2015
DOI: 10.1097/md.0000000000002113
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Based Treatment of Hepatitis C Virus Infection Reduces All-Cause Mortality in Patients With End-Stage Renal Disease

Abstract: The long-term survival of end-stage renal disease (ESRD) patients with hepatitis C virus (HCV) infection who received interferon treatment has not been extensively evaluated.The HCV cohort was the ESRD patients with de novo HCV infection from 2004 to 2011; they were classified into treated and untreated groups according to interferon therapy records. Patients aged <20 years and those with a history of hepatitis B, kidney transplantation, or cancer were excluded. The control cohort included ESRD patients withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Achieving SVR can also lessen the clinical burden of EHMs. Retrospective and prospective studies in several countries have shown that the achievement of SVR may protect against the development of mixed cryoglobulinemia, malignant lymphoma, end‐stage renal disease (ESRD) and type 2 diabetes . Clinical guidelines in Europe, therefore, recommend that HCV patients with clinically significant EHMs be prioritized for DAA treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Achieving SVR can also lessen the clinical burden of EHMs. Retrospective and prospective studies in several countries have shown that the achievement of SVR may protect against the development of mixed cryoglobulinemia, malignant lymphoma, end‐stage renal disease (ESRD) and type 2 diabetes . Clinical guidelines in Europe, therefore, recommend that HCV patients with clinically significant EHMs be prioritized for DAA treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Of nearly 50,000 HD patients included in the Dialysis Outcomes and Practice Patterns (DOPPS) study, 9.5% were HCV seropositive, but only 1% of the almost 4500 patients with prescription data and 3.7% of patients on the kidney transplant waiting list had received anti‐HCV therapy during the interferon era . These low rates of HCV treatment may have been related to the unsatisfactory safety profile of interferon and ribavirin treatment regimens, an anticipated low sustained virological response (SVR) rates in the ESRD population, or to an expected lack of clinical benefit of HCV cure in dialysis patients. It is unknown whether this has changed in the current era of the highly effective direct‐acting antiviral (DAA) agents with low treatment‐associated adverse event rates.…”
Section: Introductionmentioning
confidence: 99%
“…To date, some studies have demonstrated that dialysis patients who received antiviral treatment have significant improvements in survival, particularly patients without cirrhosis or hepatocellular carcinoma . The reduction in the risk of mortality in treated patients could potentially be sustained over 3 years The International Dialysis Outcomes and Practice Patterns Survey (DOPPS) enrolling 49,762 patients receiving HD between 1996 and 2011, showed that with antiviral treatment for HCV, the hazard ratio for adjusted all‐cause mortality was lower in treated compared with non‐treated patients, though not reaching statistical significance (0.47; 95% CI 0.17–1.26) . Another study showed that IFN‐treated HCV cohort with no cirrhosis or hepatoma have markedly reduced risk of death in the compared with that in the control cohort (hazard ratio 0.17, 95% CI 0.04–0.68) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this risk of adverse outcomes, the widely accepted and practised ‘Kidney Disease: Improving Global Outcomes’ (KDIGO) Guidelines recommend treatment for all patients with CKD and HCV infection . Successful treatment of HCV infection in such patients has been shown to improve clinical outcomes …”
mentioning
confidence: 99%